Commentary: for the children’s sake, avoid non-contrast CT - McHugh, Kieran (e-Med, 2011)
Enough literature now exists such that doing a non-contrast abdominal or chest computed tomography (CT) scan for suspected mass lesions in children borders on malpractice. Although there is great uncertainty regarding estimated radiation doses and long-term cancer risks in childhood, there is no doubt that an entirely unnecessary CT study does more harm than good. When a chest or abdominal mass is suspected in a child, only a post-intravenous contrast enhanced CT examination is needed, and a prior non-enhanced CT run exposes the child to unnecessary radiation.